European Muslims' engagement in the public sphere soft counterpublics. Issue 1 (2nd January 2016) - Soliman, Asmaa
ABSTRACT: This article addresses European Muslims' public engagement in the arts by applying the concept of counterpublics. It examines two case studies of young German Muslims whose involvement in the public sphere can be described as soft counterpublics. The term soft counterpublics denotes publics that show some characteristics of counterpublics, but are at the same time not only about 'countering'. They can be seen as 'in between' cases, neither strong counterpublics nor completely beyond counterpublics. Their art reflects a diversity of interests that are translated into public expressions and related back to their multiple identities. Motivations and themes are multi-layered. Occasionally, topics address stereotypes and negative identity representations of Muslims, which reflect important characteristics of counterpublics. However, themes can deal with a broad range of matters that go beyond this particular issue and that can be seen in isolation of counterpublics. On the one hand, there is a natural interest in the arts as a tool to express oneself, which is not a typical case of counterpublics. On the other hand, there is also the intention to speak to people through the arts. As well as wanting to reach the Muslim youth community in Germany, who can identify with their art, the case studies are also concerned about the non-Muslim German community and its perception of Muslim identity in Germany.